Assimilate The Qur'an's View with Science and Technology Perspectives - Mohammed, Datu; Aini, Qurotul; Supriyanti, Dedeh; Sulistiawati; Anggraeni, Mey (Aptisi Transactions On Technopreneurship (ATT), 2021)
Integration in the education of Muslims has become an agenda among Islamic intellectuals and activists. Where secular humanism and atheistic modernism leave Muslims with a legacy of educational dichotomy. Many contemporary Islamic educational institutions have been established since then, each with some distinctive integration models. Many Muslims advance the true integration of the Qur'an worldview in the Science and Technology curriculum whose students are at a critical stage of cognitive development, affective, spiritual, social, and ethical. This research presents qualitative reports that analyze several samples of integration models in a number of Islamic schools in Indonesia. In an effort to understand the Science and Technology Perspective this article assesses the worldview that has brought science and technology to its current stage. This research proposes a model for Islamic school education in which science and technology undergo thoughtful but holistic reconstruction, reinterpretation, and diversion of frameworks, and are organically infused with the Qur'an, and enrich 'Islamic studies' with good grounding and Science.